Antimicrobial Resistance & Migrants in Sweden: Poor Living Conditions Enforced by Migration Control Policies as a Risk Factor for Optimal Public Health Management - Mangrio Elisabeth; Mangrio Elisabeth; Paul-Satyaseela Maneesh; Sjögren Forss Katarina; Zdravkovic Slobodan; Zdravkovic Slobodan; Strange Michael; Strange Michael (Frontiers Media S.A., 2021)
Infectious diseases exacerbated by Antimicrobial Resistance (AMR) are of increasing concern in Sweden, with multi-drug resistant strains associated with new resistance mechanisms that are emerging and spreading worldwide. Existing research has identified that sub-optimal living conditions and poor access to healthcare are significant factors in the spread and incubation of AMR strains. The article considers this linkage and the effort to control the spread of AMR in relation to migrants, highlighting deficiencies in public policy where such individuals are often increasingly exposed to those conditions that exacerbate AMR. In many of the richest countries, those conditions are not accidental, but often direct goals of policies designed with the goal of deterring migrants from staying within host countries. Without engaging with the politics around migration control, the article points to urgent need for more holistic assessment of all public policies that may, however unintentionally, undermine AMR control through worsening living conditions for vulnerable groups. The consequences of prioritizing policies meant to deliberately worsen the living conditions of migrants over avoiding those conditions that accelerate AMR spread, are today made ever apparent where new AMR strains have the potential to dwarf the societal effects of the current Covid-19 pandemic.